SELF-MANAGEMENT FOR SHAPING SLEEP BEHAVIOR AT NIGHT IN SCHIZOPRENIA PATIENTS - Baiq Wahyu Rizki Purnama (Departemen Psikiatri Fakultas Kedokteran Universitas Brawijaya, 2022)
Background: Sleep disturbances in schizophrenia can be caused by abnormalities of the biological clock which are shown to be imbalanced in the sleep-wake cycle. In this case report, we report one of the patients with schizophrenia which already been hospitalized often. Objective: The purpose of this intervention is to improve the subject's adaptive behavior in the form of sleeping at night in a schizophrenia patient. Methods: This paper is a case report, which is already given applied therapy in self-management for shaping his sleep behavior at night which hopefully can help a patient with his problems. Assessments were carried out on the subject in the form of observation, interviews, giving Graphic tests, TAT, and WAIS. The results of the assessment stated that the subject could not manage his sleep schedule which interfered with his daily activities. The intervention given is using a behavioral approach with self-management methods which are arranged in 7 therapy sessions. Results: The patient can fulfill the target to be able to fall asleep well, this condition positively reduces his symptoms and agitative condition due to sleep problems. Conclusion: Self-management for shaping sleep behavior which combines psychodynamics and form of habitual condition from the patient can help to reduce their complaints and fulfill the target of remission. Keywords: self-management, sleep, behavior, schizophrenia.